2008
DOI: 10.1097/iop.0b013e31816102dd
|View full text |Cite
|
Sign up to set email alerts
|

Superior Oblique Muscle Amyloidosis Mimicking Myositis

Abstract: A 47-year-old man presented with complaints of progressive diplopia in downgaze and a painful firm mass on the left medial superior canthus. On examination, there was marked hyperemia of the superior bulbar conjunctiva of the left eye. Systemic examination revealed erythematous papules on his trunk and pulmonary infiltrates. CT of the orbits revealed a fusiform enlargement of the left superior oblique muscle and diffuse infiltration of the left temporal region. Biopsy of the left superior oblique muscle and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A review of the literature revealed 21 cases of localized EOM amyloidosis and 9 cases of systemic amyloidosis with EOM infiltration (Table 1). 2–29 The most common clinical findings were ophthalmoplegia (63.3%), diplopia (56.7%), and proptosis (30.0%). Patients with systemic amyloidosis were more likely to have multiple muscles affected (55.6% multiple muscles cf 11.1% single muscle involvement).…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature revealed 21 cases of localized EOM amyloidosis and 9 cases of systemic amyloidosis with EOM infiltration (Table 1). 2–29 The most common clinical findings were ophthalmoplegia (63.3%), diplopia (56.7%), and proptosis (30.0%). Patients with systemic amyloidosis were more likely to have multiple muscles affected (55.6% multiple muscles cf 11.1% single muscle involvement).…”
Section: Resultsmentioning
confidence: 99%
“…It can develop in association with herpes zoster virus infection, Sjögren's syndrome, Wegener's granulomatosis, amyloidosis, dabrafenib and trametinib therapy, or H1N1 influenza vaccinations. [3,4,7,9,10] In contrast, idiopathic orbital myositis is thought to be a nonspecific, inflammatory disorder affecting the extraocular muscles. [17] e histopathological features of idiopathic orbital myositis are consistent with those of idiopathic orbital inflammation and are different from those observed in common differential diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Among the six extraocular muscles, the superior, lateral, medial, and inferior rectus muscles are frequently affected in orbital myositis, whereas the superior and IObMs are infrequently involved. [1,[3][4][5][6][7]9,10,[12][13][14]16,19] Isolated myositis of the inferior oblique muscle (IObM) is rare and has been scarcely documented. [6] e IObM presents a peculiar anatomy.…”
Section: Introductionmentioning
confidence: 99%